A general framework for studying contests - Spencer Bastani; Thomas Giebe; Oliver Gürtler (ZBW - Leibniz Information Centre for Economics, 2020)
We develop a general framework to study contests, containing the well-known models of Tullock (1980) and Lazear & Rosen (1981) as special cases. The contest outcome depends on players' effort and skill, the latter being subject to symmetric uncertainty. The model is tractable, because a symmetric equilibrium exists under general assumptions regarding production technologies and skill distributions. We construct a link between our contest model and expected utility theory and exploit this link to revisit important comparative statics results of contest theory and show how these can be overturned. Finally, we apply our results to study optimal workforce composition.
Keywords: C72; D74; D81; J23; M51; 330; contest theory; symmetric equilibrium; heterogeneity; risk; decision theory